Cultural considerations in play therapy with Aboriginal children in Canada - Brady, Megan (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2015)
Aboriginal youth in Canada need mental health services that address culture as an integral component of treatment. Suffering and oppression caused by colonialism have led to collective distress among Aboriginal peoples and continue to impede the health and wellness of children. Counsellors have an ethical responsibility to recognize culture as an important construct that may influence a client’s healing and treatment preferences. Play therapy is a promising therapeutic approach that allows counsellors to utilize developmentally appropriate theoretical orientations and methods in treatment; however, current literature fails to provide adequate direction and guidelines for culturally competent practice. Counsellors can assume an active role in ensuring that all components of counselling are conducted in a culturally sensitive manner. More research is needed in this area, but this article explores cultural considerations that could be relevant to a child and family accessing play therapy services.